Investigating Factors Causing Students’ Anxiety in Speaking English - Sri Mulyani (Institut Parahikma Indonesia, 2018)
The study aimed at investigating the factors causing language anxiety of EFL learners in speaking English and how to overcome such problem. The researcher employed descriptive qualitative research by using interviews, and observations as techniques of data collection. The collected data were analyzed by using Miles and Huberman’s model consisting of three steps, namely: data reduction, data display and conclusion drawing and verification. The research findings showed some factors causing students’ anxiety in speaking English. The factors were classified into three main categories; they are psychological and linguistic factors, individual related factors, and socio-cultural factors. Psychological and linguistic factors include formal environment and classroom procedures, linguistic difficulties and the role of the instructors. Meanwhile, individual related factors consist of motivation and lack of speaking practices. Socio cultural factors include social environment and limited exposure to the target language, and self-status. This study also found some suggestions to cope with anxiety in speaking English, those are more friendly and less formal classroom, friendly and encouraging teachers/lecturers, and positive feedbacks. Many participants also recommended students to do more speaking practices outside the classroom to reduce language anxiety.